2001
DOI: 10.1159/000049519
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Parasite Infestation and House Dust Mite Sensitization in Gabonese Schoolchildren

Abstract: Background: Allergic diseases seem less prevalent in communities in less developed parts of the world, where parasite infections are highly prevalent. Altogether not much is known about the association between chronic infections with tissue and blood-dwelling parasites and atopy. Methods: In an area in Gabon endemic for blood and tissue parasites, 520 schoolchildren were parasitologically examined and skin prick-tested for a set of common environmental aeroallergens. Levels of allergen-specific IgE and polyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
80
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 21 publications
11
80
3
Order By: Relevance
“…One may therefore argue that observed effects of albendazole strike a good balance between efficacy, safety, and compliance, taking into account the possible protective effects of helminths against atopic diseases (20,21,27,29,46). If, however, a substantial worm reduction in a population is desired, a single dose of albendazole is insufficiently effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may therefore argue that observed effects of albendazole strike a good balance between efficacy, safety, and compliance, taking into account the possible protective effects of helminths against atopic diseases (20,21,27,29,46). If, however, a substantial worm reduction in a population is desired, a single dose of albendazole is insufficiently effective.…”
Section: Discussionmentioning
confidence: 99%
“…This study (registered at ClinicalTrials.gov under registration number NCT01192802) was designed as a single-center, randomized, controlled, assessor-blinded clinical trial to compare the efficacy and safety of an albendazole single-dose with a two-or three-dose regimen in school-age children residing in an In this region, soil-transmitted helminths (5,16,19), malaria, and schistosomiasis (19,21,(27)(28)(29) are endemic. Approximately 3,000 inhabitants reside in these villages, and houses typically have poor sanitation.…”
Section: Methodsmentioning
confidence: 99%
“…Despite type 2 responses being considered necessary for the development of allergies, the presence of schistosome infections in humans may reduce allergic responses in infected populations (6). Thus, Schistosoma hematobium-infected school children in Gabon had a lower prevalence of skin reactivity to house dust mites than those free of this infection (7). Therefore, the chronic down-regulation of the immune system during helminth infection evokes a regulatory environment that may impart protection from allergies (8).…”
Section: Helminth Infection Protects Mice From Anaphylaxis Via Il-10-mentioning
confidence: 99%
“…Another study showed an inverse correlation between Schistosoma mansoni infection and positive responses to aeroallergens in skin prick tests (3). In Gabon, school children infected with Schistosoma haematobium had a lower prevalence of skin reactivity to house dust mites than noninfected children (32). The mechanism involved in asthma modulation is currently being clarified, using a murine model.…”
mentioning
confidence: 99%